Clinical and genomic analysis of metastatic prostate cancer progression with a background of postoperative biochemical recurrence. (12th March 2015) - Alshalalfa, Mohammed; Crisan, Anamaria; Vergara, Ismael A.; Ghadessi, Mercedeh; Buerki, Christine; Erho, Nicholas; Yousefi, Kasra; Sierocinski, Thomas; Haddad, Zaid; Black, Peter C.; Karnes, R. Jeffrey; Jenkins, Robert B.; et al.
<x xml:space="preserve">Abstract</x> Objective To better characterize the genomics of patients with biochemical recurrence (BCR) who have metastatic disease progression in order to improve treatment decisions for prostate cancer. Methods The expression profiles of three clinical outcome groups after radical prostatectomy (RP) were compared: those with no evidence of disease (NED; n = 108); those with BCR (rise in prostate‐specific antigen [PSA] level without metastasis; n = 163); and those with metastasis (n = 192). The patients were profiled using Human Exon 1.0 ST microarrays, and outcomes were supported by a median 18 years of follow‐up. A metastasis signature was defined and verified in an independent RP cohort to ensure the robustness of the signature. Furthermore, bioinformatics characterization of the signature was conducted to decipher its biology. Results Minimal gene expression differences were observed between adjuvant treatment‐naïve patients in the NED group and patients without metastasis in the BCR group. More than 95% of the differentially expressed genes (metastasis signature) were found in comparisons between primary tumours of metastasis patients and the two other outcome groups. The metastasis signature was validated in an independent cohort and was significantly associated with cell cycle genes, ubiquitin‐mediated proteolysis, DNA repair, androgen, G‐protein coupled and NOTCH signal transduction pathways. Conclusion This study shows that metastasis development after BCR is associated with a distinct transcriptional programme that can be detected in the primary tumour. Patients with NED and BCR have highly similar transcriptional profiles, suggesting that measurement of PSA on its own is a poor surrogate for lethal disease. Use of genomic testing in patients undergoing RP with an initial rise in PSA level may be useful to improve secondary therapy decision‐making.